Energy Intensive Sectors of the Indian Economy : Path to Low Carbon Development - World Bank (World Bank, Washington, DC, 2014)
Energy Intensive Sectors of the Indian Economy: Path to Low Carbon Development is the product of a collaborative effort between the World Bank and the Government of India, under the overall leadership of the Planning Commission and the Ministry of Power, and with the financial assistance of the Department for International Development (DFID) and the Energy Sector Management Assistance Program (ESMAP). The study was requested by the Government of India to develop the analytical capacity for identifying low carbon growth opportunities up to the end of the 15th Five Year Plan (March 2032) in major sectors of the economy; and to facilitate informed decision making by improving the knowledge base and raising national and international awareness of India efforts to address global climate change. The study uses an innovative engineering based, bottom up model to examine CO2 emissions from energy use during 2007 to 2031. It focuses on sectors and areas that are expected to contribute significantly to India's future growth in CO2 emissions. The report received significant support from ministries and agencies of the Government of India, including the planning commission, the ministry of environment and forests, and the ministry of power, the central electricity authority, and the bureau of energy efficiency.